Comparison between the Linked Color and White Light Imaging Combined Score in the Evaluation of High-Risk Population of Gastric Cancer - Xiu, Jiang Zhang; Bing, Nong; Juan, Ning Jia; Yu, Huang Peng (Turkish Journal of Gastroenterology, 2021)
Background: For patients undergoing gastroscopy, it is necessary to judge whether there is Helicobacter pylori infection, atrophy/intestinal metaplasia. This study aimed to evaluate and compare the light color imaging (LCI) and white light imaging (WLI) combined score during gastroscopy. Methods: Each included patient underwent normalized gastroscopy with WLI and LCI, and all notable findings were photographed. Four endoscopists reviewed the endoscopic images of each patient. The clinical information, results of the H. pylori tests were unavailable at review. The total LCI and WLI scores of each patient were calculated and their detection in high-risk populations of gastric cancer were evaluated. The diagnostic values of LCI and WLI for intestinal metaplasia were also calculated. Results: In total, 392 patients were included in the study. The degree of inflammation and proportion of active inflammation cases were significantly higher in the H. pylori gastritis group than in the non-H. pylori gastritis group; their endoscopic manifestations were also different. The LCI combined score improved the diagnostic value of each individual observation index in the diagnosis of H. pylori infection compared with the WLI combined score. The sensitivity, specificity, and accuracy were 91.9% (91.9% vs 81.5%), 91.1% (91.1% vs 80.2%), and 95.8% (95.8% vs 93.2%), respectively. The accuracy of LCI in the diagnosis of intestinal metaplasia was higher than that of WLI (83.4% vs 69.6%). Conclusion: The LCI and LCI combined score improved the diagnosis of H. pylori gastritis and intestinal metaplasia, and it is considered valuable in identifying the high-risk population of gastric cancer.